Співвідношення локальних норм та звичаїв. - Форманюк, Вікторія Васильївна; Форманюк, Виктория Васильевна; Formanjuk.V (My University, 2011)
The article is devoted to theoretical and methodological analysis of inter- action in social relations of local norms and customs. In the article based on a comprehensive analysis of scientiﬁ c literature, the author proves his version of concept of corporate custom.
Форманюк В.В.Співвідношення локальних норм та звичаїв. / В.В. Форманюк //Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. – Одеса : Фенікс, 2011. – Вип. 43. С.
Keywords: "Локальні норми" як джерела права; "Звичаї" як джерела права; Суспільні відносини; Общественные отношения; "Обычаи" как источники права; "Локальные нормы" как источники права; "Local regulations" as a source of law; Custom" as a source of law; Public Relations